High sensitivity C-reactive protein, left ventricular mass, and systolic function in obese adolescents - Erling David Kaunang; Suryani As’ad; Sarah M. Warouw; Peter Kabo (Indonesian Pediatric Society, 2016)
Background Obesity has been associated with structural and functional cardiac muscle defects. High sensitivity C-reactive protein (hs-CRP) has been utilized as an independent predictor of future cardiovascular disease.Objective To assess for correlations between hs-CRP, left ventricular mass, and systolic function in obese adolescents.Methods This cross-sectional study was conducted from August 2013 to February 2014. Subjects were obese adolescents aged 13-18 years with a body mass index (BMI) >95th percentile, according to the 2000 Centers for Disease Control and Prevention Growth Chart. Subjects underwent laboratory testing of serum hs-CRP levels, as well as left ventricular mass and function measurements by echocardiography. Descriptive analysis was performed on patients’ characteristics and correlation analysis was done by Pearson’s test with a significance level of P<0.05.Results Subjects were 40 obese adolescents. There was no statistically significant correlation between hs-CRP and left ventricular mass (r=0.083; P=0.305). There was a moderate correlation between hs-CRP with ejection fraction (EF) (r=0.372 and P=0.009 ) and fractional shortening (FS) of the left ventricle (r=0.420 and P=0.003).Conclusion In obese adolescents, we find no correlation between hs-CRP and left ventricular mass. However, hs-CRP is moderately correlated with left ventricular EF and FS.